SUN-712 Familial 46, XY Complete Female External Sex Development with a Non-Mosaic Inherited SRY Gene Variation - Vaiani, Elisa (J Endocr Soc, 2020)
Context: SRY, an architectural transcription factor containing a SOX-related high-mobility group (HMG) box, initiates testis formation in the mammalian bipotential gonadal ridge. Inherited human SRY mutations can be associated with differences in sexual differentiation (DSD) with variable phenotypes in a family. Objective: To describe the clinical, histopathological and molecular features of a novel inherited SRY allele (pMet64Val; consensus box position 9) observed within an extensive pedigree: two 46, XY sisters with primary amenorrhea (16 and 14 years of age; probands P1 and P2), their normal father and brother, and an affected paternal XY grandaunt. Design, Setting, Participants and Outcome Measurements: Following DNA sequencing to identify the SRY mutation, hormonal studies of the probands and histopathological examination of their gonads were performed. Functional consequences of p.Met64Val (and other mutations at this site) were also investigated. Results: Breast development in P1 and P2was Tanner II and IV, respectively. Müllerian structures and gonads resembling ovaries were found in each sister. Histopathology revealed gonadal dysgenesis, gonadoblastoma and dysgerminoma. AMH/MIS, P450 SCC, and P450 aromatase were expressed in gonadoblastoma tissues. Variant p.Met64Val impaired Sox9 transcriptional activation associated with attenuated occupancy of the testis-specific enhancersEnh13 and TESCO. Conclusion: The partial biological activity of p.Met64Val SRY, maintained at the threshold of SRY function, rationalizes opposing paternal and proband phenotypes (the “the father-daughter paradox”).Sex steroids biosynthesis by gonadoblastoma may delay genetic diagnosis and recognition of gonadal tumors. Quantitative assessment of inherited SRY alleles highlights the tenuous transcriptional threshold of developmental decision-making in the bipotential gonadal ridge.